The Contribution of the Mining Sector to Socioeconomic and Human Development - McMahon, Gary; Moreira, Susana (World Bank, Washington, DC, 2014)
Many low and middle-income mineral-rich countries have experienced strong growth for a decade or longer, propelled by a rapid expansion of their mineral exports and a rise in prices of these commodities. This sustained strong economic performance goes against the accepted wisdom that even though the mining sector, like other extractive industries, can generate foreign exchange and fiscal revenues, it contributes little to sustained economic growth and, by extension, human development. Through the presentation of trends and patterns of various indicators, this paper shows that in addition to economic growth, countries rich in minerals other than oil have experienced significant improvements in their human development index (HDI) scores that are on average better than those experienced by countries without minerals. In a sample of five low and middle-income countries with relatively long histories of mining, benefits came from foreign direct investment (FDI), export revenues, and fiscal revenues. The overall impact of the mining sector was much stronger if there were infrastructure benefits and strong linkages to other industries, especially through domestic procurement. Contrary to the notion that there are no jobs in mining, in this small sample, employment related to the mining sector was very high in countries where linkages were strong, even before the multiplier and fiscal expenditure impacts were accounted for. Cooperation between the public and private sectors seemed essential to increasing such linkages. In addition, mining firms often made substantial contributions to local and regional development, at times due to legal requirements but often not. All five countries have either relatively high HDIs (compared with neighboring countries) or strongly improving HDIs.